Compressive Sensing Based Algorithms for Electronic Defence - Mishra, Amit Kumar; Verster, Ryno Strauss (Signals and Communication Technology,, 2017)
This book details some of the major developments in the implementation of compressive sensing in radio applications for electronic defense and warfare communication use. It provides a comprehensive background to the subject and at the same time describes some novel algorithms. It also investigates application value and performance-related parameters of compressive sensing in scenarios such as direction finding, spectrum monitoring, detection, and classification.